2016
DOI: 10.1128/mcb.00057-16
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Sir2-Mediated, Silent Chromatin Cohesion

Abstract: Cohesin associates with distinct sites on chromosomes to mediate sister chromatid cohesion. Single cohesin complexes are thought to bind by encircling both sister chromatids in a topological embrace. Transcriptionally repressed chromosomal domains in the yeast Saccharomyces cerevisiae represent specialized sites of cohesion where cohesin binds silent chromatin in a Sir2-dependent fashion. In this study, we investigated the molecular basis for Sir2-mediated cohesion. We identified a cluster of charged surface r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…With regard to cohesin, one study showed that mutations in the cohesin loading complex did not affect repression of reporter genes within the NTS elements (Gard et al 2009). In another study, separation-of-function mutations of SIR2 that abolished cohesion of the mating-type loci had no impact on silencing there or at the rDNA (Chen et al 2016). Thus, the evidence suggests that while Sir2 is required for cohesion; cohesion is not required for silencing.…”
Section: Intracellular Competition For Limiting Amounts Of Sir2mentioning
confidence: 98%
See 1 more Smart Citation
“…With regard to cohesin, one study showed that mutations in the cohesin loading complex did not affect repression of reporter genes within the NTS elements (Gard et al 2009). In another study, separation-of-function mutations of SIR2 that abolished cohesion of the mating-type loci had no impact on silencing there or at the rDNA (Chen et al 2016). Thus, the evidence suggests that while Sir2 is required for cohesion; cohesion is not required for silencing.…”
Section: Intracellular Competition For Limiting Amounts Of Sir2mentioning
confidence: 98%
“…Cohesin action at silent loci is regulated by the extreme C-terminal of Sir2 (Wu et al 2011). Interestingly, silencing persists in a sir2 mutant that blocks cohesion but still recruits cohesin to chromatin (Chen et al 2016). This result indicates that cohesion is dispensable for silencing even if the cohesin complex is not.…”
Section: Potential Cell Cycle Regulators Of Silent Chromatin Establismentioning
confidence: 99%